2017
DOI: 10.15252/embr.201744292
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome topology guides the Drosophila Dosage Compensation Complex for target gene activation

Abstract: X chromosome dosage compensation in requires chromosome-wide coordination of gene activation. The male-specific lethal dosage compensation complex (DCC) identifies and binds to X-chromosomal high-affinity sites (HAS) from which it boosts transcription. A sub-class of HAS, PionX sites, represent first contacts on the X. Here, we explored the chromosomal interactions of representative PionX sites by high-resolution 4C and determined the global chromosome conformation by Hi-C in sex-sorted embryos. Male and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 51 publications
10
51
0
Order By: Relevance
“…Second, the complex must spread to epigenetically marked active transcription units to disseminate the activating H4 acetylation . We and others suggested that this dissemination may involve dynamic interactions between chromosomal regions of primary binding and target genes in the active nuclear compartment . Our current study reveals that the DCC assembles at HAS already at the earliest developmental window we could interrogate by ChIP, but this binding does not immediately lead to maximal H4K16 acetylation.…”
Section: Resultsmentioning
confidence: 55%
“…Second, the complex must spread to epigenetically marked active transcription units to disseminate the activating H4 acetylation . We and others suggested that this dissemination may involve dynamic interactions between chromosomal regions of primary binding and target genes in the active nuclear compartment . Our current study reveals that the DCC assembles at HAS already at the earliest developmental window we could interrogate by ChIP, but this binding does not immediately lead to maximal H4K16 acetylation.…”
Section: Resultsmentioning
confidence: 55%
“…Dosage compensation is genetically encoded on the X chromosome in the form of ~300 high affinity binding sites (HAS) for the DCC, which are also referred to as 'chromosomal entry sites' (CES). The current model poses that the DCC first interacts with HAS on the X chromosome and then transfers to active genes in its vicinity [(Schauer et al, 2017) and reviewed in (Kuroda et al, 2016;Samata and Akhtar, 2018)]. These genes are epigenetically marked by methylation of histone H3 at lysine 36 (H3K36me3), a mark that is placed co-transcriptionally.…”
Section: Introductionmentioning
confidence: 99%
“…ChIP-seq on MNase-digested chromatin and sonicated chromatin was performed as previously described 45,87 . For spike-in ChIP-seq on MNase-digested chromatin in combination with mild sonication, S2 cells (~3*10 8 cells) after RNAi were harvested and cross-linked with 1% formaldehyde for 8 min by adding 1 mL 10× fixing solution (50 mM HEPES pH 8.0, 100 mM NaCl, 1 mM EDTA, 0.5 mM EGTA) with 10% formaldehyde [16% formaldehyde solution (w/v) methanol-fee (Thermo Fischer)] per 10 mL culture at RT.…”
Section: Methodsmentioning
confidence: 99%